Café Amazon Malaysia Online Ordering System - Zolkifli, Amirul Hazieq; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2024)
Cafe Amazon is a chain of coffee shops in Malaysia with wide selection of goods that are associated with coffee. Customer needs to queue up to the cashier to make an order and the staff needs to key in the order into the points of sale(pos) system. Thus, the objective is to develop a web-based for the customers and  stakeholders which can help streamline the ordering process . In terms of methodology, the waterfall method is used in this project. PHP, HTML ,CSS, and JavaScript are used for the web-based system and MySQL for the database. Through this Cafe Amazon Malaysia Online Ordering System, customer make an online order while the staff manage the product and receive the order online. This approach may improve business performance and customer service for stakeholders.